Pre‐Lithiation Strategies for Next‐Generation Practical Lithium‐Ion Batteries. Issue 12 (15th March 2021) - Jin, Liming; Shen, Chao; Wu, Qiang; Shellikeri, Annadanesh; Zheng, Junsheng; Zhang, Cunman; Zheng, Jim P.
Abstract: Next‐generation Li‐ion batteries (LIBs) with higher energy density adopt some novel anode materials, which generally have the potential to exhibit higher capacity, superior rate performance as well as better cycling durability than conventional graphite anode, while on the other hand always suffer from larger active lithium loss (ALL) in the first several cycles. During the last two decades, various pre‐lithiation strategies are developed to mitigate the initial ALL by presetting the extra Li sources to effectively improve the first Coulombic efficiency and thus achieve higher energy density as well as better cyclability. In this progress report, the origin of the huge initial ALL of the anode and its effect on the performance of full cells are first illustrated in theory. Then, various pre‐lithiation strategies to resolve these issues are summarized, classified, and compared in detail. Moreover, the research progress of pre‐lithiation strategies for the representative electrochemical systems are carefully reviewed. Finally, the current challenges and future perspectives are particularly analyzed and outlooked. This progress report aims to bring up new insights to reassess the significance of pre‐lithiation strategies and offer a guideline for the research directions tailored for different applications based on the proposed pre‐lithiation strategies summaries and comparisons. Abstract : This progress report reassesses the significance of pre‐lithiation strategies for the next generation lithium ion batteries and offers a guideline for the research directions tailored for different applications based on the proposed pre‐lithiation strategies summaries and comparisons.